Author Correction: Predicting biomass global warming potential with FT-NIR spectroscopy (Scientific Reports, (2025), 15, 1, (33725), 10.1038/s41598-025-10584-z) - Gyawali, Prakash; Shrestha, Bijendra; Phanomsophon, Thitima; Posom, Jetsada; Pornchaloempong, Pimpen; Sirisomboon, Panmanas; Shrestha, Bim Prasad; Funke, Axel (My University, 2026)
Correction to: Scientific Reportshttps://doi.org/10.1038/s41598-025-10584-z, published online 30 September 2025 The original version of this Article contained errors. In the original version of this article, the climate-carbon effect value was not included as introduced in AR6. As a result, in the Materials and methods section, under the subheading ‘Estimation of global warming potential and emission of greenhouse gas (GHG)’, where: “Step 1: (CO2, CH4, N2O) emissions (kg) = Mass of Fuel (kg) × Carbon emission factor (kg TJ-1) × HHV (kg TJ-1) Step 2: Total GWP = (GWP of CO2×CO2 emissions) +(GWP of CH4×CH4 emissions) +(GWP of N2O×N2O emissions)” now reads: “Step 1: GHG (CO2, CH4, or N2O) emissions (kg) = Mass of Fuel (kg) × Specific GHG emission factor (kg TJ-1) × HHV (TJ kg-1) Step 2: Total GWP (kg CO2e) = (GWP of CO2×CO2 emissions) + (GWP of CH4×CH4 emissions) + (GWP of N2O×N2O emissions)” In addition, under the subheading ‘Model development and validation’, where: “The model was optimized by selecting wavenumbers through various variable selection methods, including the Correlation Method (CM), Variance Method (VM), Co-Variance Method (COVM), and Variable Importance Projection (VIP). The spectral data were pretreated using raw spectra, standard normal variate (SNV), as well as first derivative and second derivative transformations. The following spectra pretreatment methods: Standard Normal Variate (SNV) is for corrects scatter effects and baseline variations35,” now reads: “The model was optimized by selecting wavenumbers through various variable selection methods, including the Correlation Method (CM), Variance Method (VM), Co-Variance Method (COVM), and Variable Importance Projection (VIP). The following spectra pretreatment methods: Standard Normal Variate (SNV) is for correcting scatter effects and baseline variations35,” In addition, Equations 3, 4 and 6 contained typesetting errors. As a result, Equation 3: (Formula presented.) now reads, (Formula presented.) Equation 4: (Formula presented.) now reads: (Formula presented.) And Equation 6 (Formula presented.) now reads: (Formula presented.) Furthermore, under the Results section, subheading ‘Predicting performance of biomass GWP using PLSR’, where: “The model developed with CM (reduction of 1150 wavenumber of full range to 325 wavenumber) of 1st derivative spectra, gave best performance with R2P was 0.87 (Table 4).” now reads: “The model developed with COVM (reduction of 1150 wavenumber of full range to 325 wavenumber) of 1st derivative spectra, gave the best performance with R2P was 0.85 (Table 4).” Under the subheading ‘Prediction result of HHV using PLSR’, where: “This approach reduced the number of variables from 1150 to 365 wavenumbers, significantly enhancing the model’s performance (R2C of 0.98 and R2P of 0.87)” now reads: “This approach reduced the number of variables from 1150 to 365 wavenumbers, significantly enhancing the model’s performance (R2C of 0.98 and R2P of 0.86)” Under the subheading ‘Regression coefficient and x-loading of GWP model’, where: “Prominent peaks were identified and the bond vibration interpretation is shown in Table 7 and the vibration indicated by Workman and Weyer38 at the wavenumbers in bold were not found or not related to biomass.” now reads: “Prominent peaks were identified, and the bond vibration interpretation is shown in Table 7, which was indicated by Workman and Weyer38.” Equation 8: GWP for CO2, or CH4, or N2O Emissions = (1×CO2 Emission) or (29.8×CH4 Emission) or (273×N2O Emission) = (1×112 HHV) for CO2 Emission or (29.8×30 HHV) for CH4 Emission or (273×4 HHV) for N2O Emission = 112.0×HHV for CO2 Emission or 894.0×HHV for CH4 Emission or 1092.0×HHV for N2O Emission and GWP total = 2098.0 (HHV, TJ kg-1) = 0.000002098 kJ kg-1 = 0.000002098 Jg-1 now reads: GWP for CO2, or CH4, or N2O Emissions = (1×CO2 Emission) or (27.2×CH4 Emission) or (273×N2O Emission) = (1×112 HHV) for CO2 Emission or (27.2×30 HHV) for CH4 Emission or (273×4 HHV) for N2O Emission = 112.0×HHV for CO2 Emission or 816.0×HHV for CH4 Emission or 1092.0×HHV for N2O Emission and GWP total (kg CO2e) = 2020.0 (HHV, TJ kg-1) = 0.000002020 kJ kg-1 = 0.000002020 J g-1 Moreover, Tables 1 and 3 have been corrected. Incorrect Table 1: Remarks IPCC guideline Calculation of CO2 emission Higher Heating Value = 17932000 J kg-1 CO2 emission factor = 112 kg TJ-1, we can follow these steps: Convert HHV to TJ kg-1: Since 1 TJ = 1012 J, we need to convert the HHV from J kg-1 to TJ kg-1: HHV in TJ kg-1 = 17932000 J kg-1 / 1012 = 1.7932×10-3 TJ kg-1 CO2 emission (kg) = Mass of fuel (kg) × CO2 emission factor (kg TJ-1) × HHV (TJ kg-1) CO2 emission (kg) = 1 kg × 112 kg TJ-1 × 0.017932 TJ kg-1 Therefore, the CO2 emission from stationary fuel combustion with an HHV of 17932000 J kg-1 and using the default CO2 emission factor of 112 kg TJ-1 would be approximately 2.0083×10-3 kg of CO2 per kg of fuel. CO2 emission factor: 112 kg dry matter TJ-1 (typical for wood combustion) Calculation of CH4 emission Hight Heating Value = 17932000 J kg-1 CH4 emission factor = 30 kg TJ-1 Convert HHV unit to TJ kg-1 1 TJ= 1012 J HHV from J kg-1 to TJ kg-1: HHV in TJ kg-1 = 17932000 J kg-1 / 1012 = 1,7932×10-5 TJ kg-1 CH4 emission (kg) = Mass of Fuel (kg) × CH4 emission factor (kg TJ-1) × HHV (TJ kg-1) CH4 emission (kg) = 1 kg × 30 kg TJ-1 × 1,7932×10-5 TJ kg-1 CH4 emission (kg) = 5.3796×10-4 kg of CH4 per kg of fuel CH4 emission factor: 30 kg dry matter TJ-1 Calculation of N2O emission Hight Heating Value = 17932000 J kg-1 N2O emission factor = 4 kg TJ-1 Convert HHV unit to TJ kg-1 1 TJ = 1012 J HHV from J kg-1 to TJ kg-1: HHV in TJ kg-1 = 17932000 J kg-1 / 1012 = 1.7932 ×10-5 TJ kg-1 N2O emission (kg) = Mass of Fuel (kg) × N2O emission factor (kg TJ-1) × HHV (TJ kg-1) N2O emission (kg) = 1 kg × 4 kg TJ-1 × 1.7932×10-5 TJ kg-1 N2O emission (kg) = 7.1728×10-5 kg of N2O per kg of fuel N2O emission factor 4 kg dry matter /TJ The concept of global warming potential (GWP) was introduced in IPCC –AR1 (Shine et al. 1990) to compare the greenhouse effects of different greenhouse gases relative to a reference gas, normally taken as carbon dioxide, under this definition, CO2 would have a GWP value of 1. Total GWP = (GWP of CO2×CO2 emissions)+(GWP of CH4×CH4 emissions)+(GWP of N2O×N2O emissions) Total GWP =1×2.0083×10-3+29.8× 5.379 ×10-4+273×7.1728×10-5 Total GWP=0.0376 kg CO2e This calculation is by 100 years based GWP of emission gases followed AR6 7 Correct Table 1: Remarks IPCC guideline Calculation of CO2 emission Higher Heating Value = 17932000 J kg-1 CO2 emission factor = 112 kg TJ-1, we can follow these steps: Convert HHV to TJ kg-1: Since 1 TJ = 1012 J, we need to convert the HHV from J kg-1 to TJ kg-1: HHV in TJ kg-1 = 17932000 J kg-1 / 1012 = 1.7932×10-5 TJ kg-1 CO2 emission (kg) = Mass of fuel (kg) × CO2 emission factor (kg TJ-1) × HHV (TJ kg-1) CO2 emission (kg) = 1 kg × 112 kg TJ-1 × 1.7932 × 10-5 TJ kg-1 Therefore, the CO2 emission from stationary fuel combustion with an HHV of 17932000 J kg-1 and using the default CO2 emission factor of 112 kg TJ-1 would be approximately 2.0083 × 10-3 kg of CO2 per kg of fuel. CO2 emission factor: 112 kg dry matter TJ-1 (typical for wood combustion) Calculation of CH4 emission Higher Heating Value = 17932000 J kg-1 CH4 emission factor = 30 kg TJ-1 Convert HHV unit to TJ kg-1 1 TJ= 1012 J HHV from J kg-1 to TJ kg-1: HHV in TJ kg-1 = 17932000 J kg-1 / 1012 = 1,7932×10-5 TJ kg-1 CH4 emission (kg) = Mass of Fuel (kg) × CH4 emission factor (kg TJ-1) × HHV (TJ kg-1) CH4 emission (kg) = 1 kg × 30 kg TJ-1 × 1,7932×10-5 TJ kg-1 CH4 emission (kg) = 5.3796×10-4 kg of CH4 per kg of fuel CH4 emission factor: 30 kg dry matter TJ-1 Calculation of N2O emission Higher Heating Value = 17932000 J kg-1 N2O emission factor = 4 kg TJ-1 Convert HHV unit to TJ kg-1 1 TJ = 1012 J HHV from J kg-1 to TJ kg-1: HHV in TJ kg-1 = 17932000 J kg-1 / 1012 = 1.7932 × 10-5 TJ kg-1 N2O emission (kg) = Mass of Fuel (kg) × N2O emission factor (kg TJ-1) × HHV (TJ kg-1) N2O emission (kg) = 1 kg × 4 kg TJ-1 × 1.7932×10-5 TJ kg-1 N2O emission (kg) = 7.1728×10-5 kg of N2O per kg of fuel N2O emission factor 4 kg dry matter /TJ-1 The concept of global warming potential (GWP) was introduced in IPCC –AR1 (Shine et al. 1990) to compare the greenhouse effects of different greenhouse gases relative to a reference gas, normally taken as carbon dioxide, under this definition, CO2 would have a GWP value of 1. Total GWP = (GWP of CO2×CO2 emissions) + (GWP of CH4×CH4 emissions) + (GWP of N2O×N2O emissions) Total GWP = 1×2.0083×10-3+ 27.2× 5.3796 × 10-4+ 273×7.1728×10-5 Total GWP= 0.03622 kg CO2e This calculation is by 100 years based GWP of emission gases followed AR6 7 Incorrect Table 3: Calibration set Prediction set Parameter Method NT NC Max Min Mean SD NP Max Min Mean SD GWP IPCC Guidelines 197 147 0.03905 0.03080 0.03564 0.00180 50 0.038943 0.033002 0.03577 0.00165 HHV (J g-1) Bomb Calorimeter 197 147 18616 16405 16976 910 50 17950 15268 17051 787 Correct Table 3: Parameter Method NT Calibration Set Prediction Set NC Max Min Mean SD NP Max Min Mean SD GWP (kg CO2e) IPCC Guidelines 197 147 0.03905 0.03080 0.03564 0.00180 50 0.038943 0.033002 0.03577 0.00165 HHV (J g-1) Bomb Calorimeter 197 147 18616 16405 15268 910 50 17950 16976 17051 787 Finally, the legends of Tables 4 and 7 have been updated: “Table 4: Prediction of GWP of biomass of fast-growing tree and agriculture residue by PLSR. N: Number of samples in calibration set, R2c: coefficient of determination of calibration set, n: number of samples in prediction set, R2p: coefficient of determination of prediction set, RPD: ratio of prediction to deviation, CM: correlation method, VM: variance method, COVM: co-variance method, VIP: variable. Significant values are in [bold].” now reads: “Table 4. Prediction of GWP of biomass of fast-growing tree and agriculture residue by PLSR. N: Number of samples in calibration set, R2c: coefficient of determination of calibration set, n: number of samples in prediction set, R2p: coefficient of determination of prediction set, RPD: ratio of prediction to deviation, CM: correlation method, VM: variance method, COVM: co-variance method, VIP: variable important projection, FstDev: 1st derivative, SecDev: 2nd derivative. Significant values are in [bold].” “Table 7. The function groups corresponding to the wavenumber shown in regression coefficient plot and x-loading plot of models for GWP and HHV. *1ν, fundamental stretching vibration; 2ν, 1st overtone of fundamental stretching vibration; 3ν, 2nd overtone of fundamental stretching vibration; 5ν, 4th overtone of fundamental stretching vibration; 1δ, fundamental bending (deformation) vibration; 3δ, 2nd overtone of fundamental bending (deformation) vibration; 1, symmetric stretching vibration; 2, bending vibration; 3, asymmetric stretching vibration; and + is combination. now reads: “Table 7. The function groups corresponding to the wavenumber shown in regression coefficient plot and x-loading plot of models for GWP and HHV. 1ν, fundamental stretching vibration; 2ν, 1st overtone of fundamental stretching vibration; 3ν, 2nd overtone of fundamental stretching vibration; 5ν, 4th overtone of fundamental stretching vibration; 1δ, fundamental bending (deformation) vibration; 3δ, 2nd overtone of fundamental bending (deformation) vibration; and + is combination.” The original version of this Article has been corrected.